The Role of Artificial Intelligence on Market Performance: Evidence from Scientific Review - Desta, Endalkachew; Amantie, Chalchissa (Journal of Economics and Behavioral Studies, 2024)
The study’s primary purpose was to review studies on the role of artificial intelligence in market performance. Artificial intelligence significantly impacts market performance by providing data analysis, personalization, demand forecasting, pricing optimization, customer support automation, risk assessment, and enhanced decision-making capabilities. By leveraging artificial intelligence (AI) effectively, Businesses can improve their competitiveness, improve customer satisfaction, increase revenue, and achieve sustainable growth in the market. A thorough assessment of the literature was done, and screening standards were applied, all to improve the study. Based on the inclusion and exclusion criteria for the articles, data extraction was done by Preferred Reporting Items for Systematic Reviews and Meta-Analyses. 45 published articles were analyzed, and significant data was extracted. The review’s findings collectively emphasize the crucial role of AI in enhancing market performance by improving sales, customer satisfaction, demand forecasting, pricing optimization, risk mitigation, and decision-making processes. As AI continues to advance, further research and practical implementations will likely uncover additional benefits and insights into its impact on market performance. To help more scholars understand and advance the numerous theories and models related to the topic, this concept overview provides guidance.